Population estimation of the Euphrates softshell turtle Rafetus Euphraticus in the Central Marshes (UNESCO site) (Baghdad Science Journal, 2024)
The Euphrates softshell turtle Rafetus euphraticus was classified as Endangered species on the IUCN Red List and is thought to have undergone large, recent population declines. Species information in Iraq is limited to a few rapid surveys with little detailed information on breeding and distribution. The study aimed to estimate the population of R. euphraticus in the Central Marshes using simple extrapolation of the count. Quadrate methodology 5 km2 size each was used to record the distribution of Euphrates softshell turtles within the study site and ten surveys were carried out from October 2021 to September 2022 except for the hibernation season (December, January and February). Turtles were recorded inside the water by setting nets in certain areas in the Central Marshes. Simple extrapolation of our counts to the entire Central Marshes suggested a maximum population size of 2526.55 individuals/ total area (219,700 ha). The Central Marshes is an important site for R. euphraticus as a total of 46 individuals were recorded.